Biological Treatment of Knee Osteoarthritis. The Role of Mesenchymal Stem Cells and Platelet‐Rich Plasma - Zazirnyi, I. M. (TERRA ORTHOPAEDICA, 2024)
Summary. Osteoarthritis (OA) is the most common joint disease, which is associated with growing population ageing. Beyond conventional medical and surgical interventions, there is an increasing number of “biological” therapies. These therapies may have a limited evidence base and, for this reason, are often only afforded brief reference (or completely excluded) from current OA guidelines. The aim of this review was to analyze current evidence regarding mesenchymal stem cells (MSCs) therapy and platelet-rich plasma (PRP). There is some evidence to suggest symptomatic improvement with MSCs injection in knee OA, with the suggestion of minimal structural improvement demonstrated on MRI, and there are positive signals that PRP may also lead to symptomatic improvement, though variation in preparation makes inter-study comparison difficult. Although controlled studies have been conducted to evaluate effectiveness in OA, they have been often of small size, limited statistical power, uncertain blindness, and using various methodologies. These deficiencies leave open the question of whether they have been validated as effective therapies in OA. The conclusions of this review are that all biological interventions definitely require clinical trials with robust methodology to assess their efficacy and safety in the treatment of OA beyond contextual and placebo effects.